Educação musical, marxismo e o conflito entre a reprodução e a superação do Capital - Costa, Yuri Coutinho Ismael da (2012)
The academic field of music education has been consolidating significantly in the last 30 years. This period, in turn, has been marked by profound social changes: economic crises that appears in increasingly smaller intervals; the deepening of social inequality; the remarkable fragmentation that ravages individuals and the reflux of the organization of the explored classes; the mass diffusion of individualistic and conservative political ideologies, the process of intensive implementation of the Capital and its determinants through the deepening of economic globalization. Given this complex scenario, emerges a problem that has been poorly treated by our field: how does music education fit into this context? How the social determinants of our time affects music-education? Thus, the goal of this dissertation is to analyze the relationship between music education, the struggle between Labor and Capital and the construction of social being nowadays. I proposed the following specific objectives: to characterize the conflict between Labor and Capital; to point out how the political ideologies of capitalism, from those that advocate its reproduction to those that argue for its overcome them, influences human praxis, in particular education; to think about the characteristics of music education today, its possibilities and challenges before our historical time; and identify how the critique of capital has been developed by researchers of the field. I employed as the main critical-analytical references the historical and dialectical materialism and the Marxian- Lukacsian ontology. I conclude by arguing that the analysis of the field of music education, taking into account the limits of this practice, enables a significant deepening of understanding of the current configuration of our society. However, critical analyzes performed to date and circulated by the academic journal Revista da ABEM, published by the Associação Brasileira de Educação Musical, offer only partial critiques to the relationship between music education and the determinants of capitalist society, which demonstrates the need to resume the critique of social totality, an essential characteristic of the Marxist critical ontology.